2015
DOI: 10.3390/pathogens4020199
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Methicillin-Resistant Staphylococcus Aureus in Sputum Specimens from Patients with Hospital-Associated Pneumonia Using a Novel Multilocus Pcr Assay

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a significant cause of hospital-associated pneumonia (HAP). The rapid identification of MRSA would be beneficial for early diagnosis. The study aimed to evaluate a multilocus, fluorescence-based PCR assay based on the detection of mecA and nuc genes for identification of S. aureusin lower respiratory tract (LRT) specimens. Sensitivity and specificity of the PCR assay were analyzed. Clinical evaluation for the assay was performed using LRT specimens from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…All isolated bacteria which they are methicillin resistant and methicillin sensitive were tested for mecA gene by using PCR. The results of mecA of present study indicated that all isolated Staphylococci speceis were harboring mecA gene with the product size 533 bp except S. vitulinus as shown in figure (1) and these results were in agreement with [31]. In addition to above results, the results showed that mecA gene was not found in other isolated bacteria except one isolates of K. rosea with same mecA (533bp) as appeared in figure (2).…”
Section: Molecular Detection Of Mecasupporting
confidence: 86%
“…All isolated bacteria which they are methicillin resistant and methicillin sensitive were tested for mecA gene by using PCR. The results of mecA of present study indicated that all isolated Staphylococci speceis were harboring mecA gene with the product size 533 bp except S. vitulinus as shown in figure (1) and these results were in agreement with [31]. In addition to above results, the results showed that mecA gene was not found in other isolated bacteria except one isolates of K. rosea with same mecA (533bp) as appeared in figure (2).…”
Section: Molecular Detection Of Mecasupporting
confidence: 86%
“…According to CLSI guidelines MRSA can be confirmed by detection of mecA gene. PCR based amplification of mecA is commonly used for detection of MRSA 14 . FDA approved PCR methods 6 have sensitivity in the range of 82 to 100 %.…”
Section: Confirmation Of Mssa By Pcr: Absence Of Meca Gene Amplificationmentioning
confidence: 99%
“…A study 14 identified a novel multi locus fluorescence based PCR where mecA and nuc gene were detected simultaneously. The specificity of this PCR was shown to be over 96 % if PCR copy number reaches certain threshold.…”
Section: Confirmation Of Mssa By Pcr: Absence Of Meca Gene Amplificationmentioning
confidence: 99%
“…93 Advances in molecular diagnostics, such as multivalent polymerase chain reaction analysis or automated microscopy, offer the ability to perform rapid real-time identification of pathogens, which can be confirmed with companion microbiological methods to measure antibiotic susceptibility profiles and the spectrum of pathogens. [94][95][96] In conjunction with rapid diagnosis, targeting specific virulence factors with AVAs may provide increased potential for individualized therapy in a bench-to-bedside approach to therapy. Early diagnosis may also open the door for prophylaxis and the potential to avoid inappropriate use of broadspectrum antibiotics before or at the time of clinical diagnosis of pneumonia.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%